Wladimir Vogel as a mediator: John Cage in Donaueschingen, Zurich, and Milan - Farolfi, Manuel (Schweizer Jahrbuch für Musikwissenschaft, 2026)
American composer John Cage travelled to Europe three times in the post-war period. These visits have received significant scholarly attention due to their importance in the trans-Atlantic musical interactions following the war. Studies have focused on the reception of Cage’s music and aspects of cross-fertilisation, with considerable effort dedicated to rebuilding early contacts and their role in these processes. Despite such extensive research, however, the connection between Cage and Russian-German composer Wladimir Vogel has remained overlooked. Building on the information disclosed in a letter from Cage to Vogel, preserved at the Zentralbibliothek in Zurich, this essay seeks to illuminate the encounter between the two composers in Milan in 1949 and Vogel’s subsequent role as a mediator for the concerts Cage held in Donaueschingen, Zurich, and Milan in 1954.